What's Critical about Critical Infrastructure?. Issue 1 (2nd January 2017) - Steele, Wendy; Hussey, Karen; Dovers, Stephen
Abstract: Critical infrastructure (CI) has received much attention in research, policy and political discussions in recent years, following concern over exposure of infrastructure to terrorist attack, disruption through disasters, rising awareness of the interdependent nature of infrastructure in modern urban systems, and changes in the ownership of and responsibility for infrastructure assets. In this paper, we explore the implications of different framings of both "critical" and "infrastructure", through two questions: critical how and for whom; critical when and at what scale? Framings of CI, and their increasingly important manifestations in policy and law, have deep but too-often unexposed implications: the lines drawn between what is defined as critical and that which is not concerns not only the physical or informational assets, but the inclusion/exclusion of communities and their places and values as important aspects of modern urban governance. We argue that a better understanding of what is critical about urban infrastructure is not just recognition of their vulnerability and interconnectedness, but also of the key linkages between critical infrastructure and human and environmental system integrity and equity within the context of capitalist urbanisation.